(untitled) (Nigerian Journal of Technology, 2018)
In Nigeria today, polyethylene or water sachet is a major environmental pollutant, a non-biodegradable material. The usefulness of this pollutant (polyethylene) in the highway industry was investigated by studying its effects on some selected properties of Hot Mix Asphalt, such as, bulk density, stability and flow of the asphalt concrete mix. Specimen preparation was done using Marshall Mix design procedure. The optimum binder content was determined as 5.20% and three samples each for five variations of polyethylene content (2%, 4%, 6%, 8% and 10%) by weight of optimum binder content. It was observed from the study, that the stability and density of asphalt increased with polyethylene content, while a linear reduction in the flow and penetration values was observed with polyethylene content. The optimum modifier content value of 8% by weight of the optimum bitumen content. Models were also developed whose predictive values corroborated well with experimental values with acceptable coefficient of correlation values. Bitumen modified with polyethylene improved the engineering properties of asphalt which therefore means that usage of this waste product in the asphalt production for roadwork is an effective and economical way of managing this waste. http://dx.doi.org/10.4314/njt.v38i1.1